Experiences of and support for black women in ecology, evolution, and marine science - Nikki Traylor-Knowles; Anamica Bedi de Silva; Anjali D. Boyd; Karlisa A. Callwood; Alexandra C. D. Davis; Giselle Hall; Victoria Moreno; Cinda P. Scott (Frontiers in Marine Science, 2023)
Systemic racism and sexism are well documented in ecology, evolution, and marine science. To combat this, institutions are making concerted efforts to recruit more diverse people by focusing on the recruitment of Black people. However, despite these initiatives, white supremacy culture still prevails. The retention of Black people in ecology, evolution, and marine science has not increased in the ways that were hoped for. This is particularly true for Black women, who struggle to find a safe working environment that values their contributions and allows them to openly celebrate their own culture and identity. In this perspective article, we discuss the challenges that Black women face every day, and the needs of Black women to thrive in ecology, evolution, and marine science. We have written this directly to Black women and provide information on not only our challenges, but our stories. However, readers of all identities are welcome to listen and examine their role in perpetuating systemic racism and sexism. Lastly, we discuss support mechanisms for navigating ecology, evolution, and marine science spaces so that Black women can thrive.